The Role of Hydroxycinnamic Acid Amide Pathway in Plant Immunity - Liu, Saifei; Jiang, Jincheng; Ma, Zihui; Xiao, Muye; Yang, Lan; Tian, Binnian; Yu, Yang; Bi, Chaowei; Fang, Anfei; Yang, Yuheng (Frontiers in Plant Science, 2022)
The compounds involved in the hydroxycinnamic acid amide (HCAA) pathway are an important class of metabolites in plants. Extensive studies have reported that a variety of plant hydroxycinnamamides exhibit pivotal roles in plant-pathogen interactions, such as p-coumaroylagmatine and ferulic acid. The aim of this review is to discuss the emerging findings on the functions of HCAAs accumulation associated with plant defenses against phytopathologes, and the mechanism of HCAAs involved in plant immune responses (such as reactive oxygen species, cell wall response, plant defense hormones, and stomatal immunity). However, these advances have also revealed the complexity of HCAAs participated in plant defense reactions, and many mysterys remain to be revealed. This review provides an overview of the mechanistic and conceptual insights obtained so far and highlights areas for future exploration of phytochemical defense metabolites.